2009
DOI: 10.2164/jandrol.108.005694
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Treatment of Male Infertility: Promises and Pitfalls

Abstract: Approximately 50% of infertility issues are attributable to male factors. A number of different factors may result in similar reductions of sperm count or motility and affect sperm morphology. Not only is the etiology of male infertility difficult to understand, but it is equally challenging to treat male infertility because of its etiological heterogeneity. Because of complex and incomplete knowledge of the underlying causes, most infertile men are described as idiopathically oligozoospermic and/or asthenozoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 195 publications
(174 reference statements)
0
37
0
Order By: Relevance
“…The hypothalamic pituitary gonadal axis plays an important role in regulation of the different stages of reproductive activities such as sexual differentiation, sexual maturity, reproductive and sexual behavior, etc [34,48]. Earlier observations similarly suggested that diabetes in humans leads to significant alteration in endocrine regulation and impairment, which indicates that diabetes has the potential to derange the hypothalamic pituitary gonadal axis [16,25,26,47].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamic pituitary gonadal axis plays an important role in regulation of the different stages of reproductive activities such as sexual differentiation, sexual maturity, reproductive and sexual behavior, etc [34,48]. Earlier observations similarly suggested that diabetes in humans leads to significant alteration in endocrine regulation and impairment, which indicates that diabetes has the potential to derange the hypothalamic pituitary gonadal axis [16,25,26,47].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal assay of the FSH, LH and testosterone is useful in the management of the male infertility, and for initiation of spermatogenesis and maturation of spermatozoa [3,15]. In the oligozoospermic men higher concentration of FSH is considered to be a reliable indicator of germinal epithelial damage or primary testicular failure [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Germ cell development is dependent on the balanced endocrine interplay of the hypothalamus, the failure of pituitary to secret FSH and LH will result in disruption of testicular function leading to infertility [1][2][3]. In addition, Yq, long arm of Y chromosome, contains at least one gene that is responsible for spermatogenesis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many andrological studies claimed that GH exerts its effects either directly and/or indirectly in the regulation of spermatogenesis. Firstly, direct effects are believed to be through GH receptors localized on hypothalamus and gonads (2), thereby Sertoli cell functions and secondly, indirect effects contribute to the GH coordination of hormones of hypothalamo-pituitary-testicular axis such as follicle stimulating hormone (FSH), leutinizing hormone (LH) and testosterone to influence testicular functions (3). Thus, it seems apparent that GH at least in part targets spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%